(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article reflects on the changes in the composition of food products produced taking into account the knowledge, attitudes, tastes and regions of residence of today’s consumers. It discusses market factors that influence the activities of food manufacturers and highlights the significance of these factors in the present day. The increasing consumer awareness and cultural consumption practices year by year are explained as driving forces behind the demand for ethically produced food products. The article also elaborates on the goals of ethical food production. It also provides a comparative analysis of digitization rates in the food trade over the years. The study recommends strategic approaches to address these challenges, such as sustainable agriculture, the introduction of digital technologies, the diversification of logistics chains, and the strengthening of international cooperation. In conclusion, the study emphasizes the role of government support for small-scale producers (such as household farms) in ensuring the stability of the food market.